Marketing Through Play: Integrating Gamification and User Experience to Drive E-Commerce Engagement and Loyalty - Raditha Hapsari; Ananda Sabil Hussein; Noor Awanis Muslim; Thitiya Thongkern (Universitas Pendidikan Ganesha, 2025)
The development of cutting-edge era forces market attractiveness and competitiveness worldwide. The recovery from the Covid-19 pandemic has triggered changes in the workplace environment and people's shopping behavior. This study examined the structural relationship between factors affecting customer loyalty, engagement, and experience through technology adoption. This study aims to investigate the structural relationships among perceived ease of use, gamification, user experience, customer engagement, customer enjoyment, and customer loyalty in the context of e-commerce. The novelty of this study lies in integrating the UX–Loyalty and Gamification–Engagement models within TAM to reveal both functional and hedonic pathways to customer loyalty in e-commerce. Grounded in technology adoption and customer engagement theories, the study employs PLS-SEM to test how gamification and ease of use shape user experience, which in turn drives engagement, enjoyment, and loyalty. The results of this study indicate that user experience, customer engagement, and enjoyment significantly predict customer loyalty. Surprisingly, this research showed that experience has no significant effect on customer loyalty. Furthermore, this study could enlarge the literature review about customer loyalty.